2011
DOI: 10.1140/epje/i2011-11089-4
|View full text |Cite
|
Sign up to set email alerts
|

Bethe-Peierls approximation for linear monodisperse polymers re-examined

Abstract: Bethe-Peierls approximation, as it applies to the thermodynamics of polymer melts, is reviewed. We compare the computed configurational entropy of monodisperse linear polymer melt with Monte Carlo data available in the literature. An estimation of the configurational contribution to the total liquid's C(p) is presented. We also discuss the relation between the Kauzmann paradox and polymer semiflexibility.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…where Ψ i = 1 + λξ i . As we have shown in our previous work, 37 the derived approximation for the partial partition function is equally applicable to the Cayley tree of x generations capturing a chain connected to its z ′ = 2(z − 1) + (x − 2)(z − 2) nearest neighbor sites.…”
Section: Density Profile Of Semi-flexible Chain In Presence Of Ad-sor...mentioning
confidence: 71%
See 4 more Smart Citations
“…where Ψ i = 1 + λξ i . As we have shown in our previous work, 37 the derived approximation for the partial partition function is equally applicable to the Cayley tree of x generations capturing a chain connected to its z ′ = 2(z − 1) + (x − 2)(z − 2) nearest neighbor sites.…”
Section: Density Profile Of Semi-flexible Chain In Presence Of Ad-sor...mentioning
confidence: 71%
“…Along with using more advanced in terms of correlations taken into account approximation, the present study remedies this omission by using the modified lattice coordination number that distinguishes between trans and gauche configurations of the polymer chain, as has been suggested previously by Silberberg. 33 In our former study, 37 we applied the Bethe-Peierls approximation 38,39 to the study of the uniform polymer melts and demonstrated the complete agreement of this approach with quasi-chemical approximation. The present work describes an extension of our earlier studies to the case of non-uniform polymer melts in the presence of adsorbing surface.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations